Військова конференція ОУН(Б) 1942 р. і розробка планів зі створення українських збройних сил - Патриляк, І.; Пагіря, О. (З архівів ВУЧК-ГПУ-НКВД-КГБ, 2008)
The authors, used the documents of former soviet secret services, investigated the process of organizational formation of Ukrainian Insurgent Army in 1942.